Side effects related to thermogenic supplements containing synphine (Research, Society and Development, 2021)
Food Supplements (SA) are widely used by athletes and practitioners of physical activities, as a way to complement their diet, whether for gain, weight loss or other specific goals. Thermogenics, in this case, are composed of substances that have the ability to speed up metabolism, offering greater calorie burning and reducing appetite. On the other hand, they may contain substances, such as Synephrine, which can harm health. Thus, this research aims to investigate the chemical composition of thermogenic supplements containing synephrine. The research was divided into two stages. Firstly, the label of these supplements was analyzed, collected on the internet site, and later, a systematic literature review was carried out, in which scientific articles were selected, from 2010 to 2019, within the database from SciELO, PubMed, Bireme, Google Scholar, and LILACS, using the descriptors: Food supplements/ food supplements; Synephrine/synephrine; Slimming/slimming; Thermogenic/ thermogenic. For meeting the inclusion criteria, scientific articles and dissertations were chosen, presenting themselves in full, that is, full text, being made available in Portuguese and English, which were in accordance with the proposed theme. The study was based on approaches to the influence of supplements on quality of life, thermogenic synephrine-based and the side effects of such products. As a result, the research concluded that synephrine, being similar to ephedrine, develops effects on the cardiovascular system, which can generate cases of increased blood pressure, increased heart rate, arrhythmias and stroke, especially when associated with caffeine. Some studies have also reported that synephrine can cause liver and kidney problems. Therefore, it is concluded that such compounds when not used correctly and without proper guidance, can cause serious damage to health.